Symptoms of Modernity : Jews and Queers in Late-Twentieth-Century Vienna - Bunzl, Matti, 1971- (Book collections on Project MUSE., 2004)
In the 1990s, Vienna's Jews and queers abandoned their clandestine existence and emerged into the city's public sphere in unprecedented numbers. 'Symptoms of Modernity' traces this development in the context of Central European history.